TRANFORMASI DARI STRUKTURAL POLITIK KE KULTURAL: DINAMIKA PENERAPAN SYARIAH ISLAM (BANK SYARIAH DAN JILBAB SEBAGAI STUDI KASUS DI INDONESIA) - Dwi Purwoko (Universitas Nasional, 2018)
Religious awareness in society is increasing. This can be seen from the increasingly widespread use of the veil in society, the emergence of awareness to save money in syraiah institutions, the rise of people uintuk go to the holy land of Mekakh both Umtoh and hajj, the number of pengajian, tabligh akbar and the emergence of Sufi urban mostly jamaahnya young Muslim well established and so on. Regardless of the symbolic or subtasni it seems that the dynamics of the application of syaraiah have appeared cultivally in the cultural line after the